TRANSBOUNDARY ENVIRONMENTAL POLLUTION: UNDERSTANDING THE INTRICACIES OF INTERNATIONAL LAW (The Pretoria Student Law Review, 2021)
Faced with the enormity and urgency of international environmental problems the world has experienced a political awakening. Although environmental issues are not new for international relations, world leaders have increasingly brought environmental issues from the sidelines to the centre of their negotiation agendas. International conferences and treaties regarding global warming and ozone depletion are but few signs that the world has entered a new age of environmental diplomacy in which environmental issues will share centre-stage with more traditional economic and military concerns. In response to this concern governments, legislatures, and the courts have produced a labyrinth of draft bills, amendments to existing legislation, regulations, drafts of international treaties, and judicial decisions, all creating legal controls of pollution. In order to ascertain scientific information and technological data royal commissions, presidential enquiries, governmental departments, and international agencies have undertaken extensive research programs. Paralleling these developments, international environmental law has started to become a new and an emerging academic discipline. A growing number of commentators, diplomats, and practitioners are concentrating on transboundary and global environmental issues. There has also been a significant increase in the number of law schools all over the world that have started focussing towards this subject. The regime of international environmental law is mainly composed of treaties, customs; general principles of international law and opinio juris. In an attempt to use customary international law to protect the environment, commentators have spent the last two decades in elaborating the rules of state responsibility and liability specifically to address the issues related to transboundary pollution. States have begun to build on this liability regime towards the development of international agreements designed to prevent harmful environmental activity.
Keywords: international environmental problems; environmental issues; international conferences; treaties; global warming; ozone depletion; environmental diplomacy; traditional economic; military concerns; legal controls of pollution; judicial decisions